2018
DOI: 10.1016/j.clinph.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates of word processing deficits in isolated reading and isolated spelling disorders

Abstract: Our study is the first to specify the underlying neurophysiology of word processing deficits associated with isolated literacy deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…More research is needed in order to explain these differences between isolated spelling and reading disorder. However, recent research has shown that reading and spelling disorder are related to distinct neurocognitive profiles (36). We speculate that these underlying differences in neurocognitive profiles result in behavioral differences and thereby explain the comorbidity between SLD and psychopathological symptoms.…”
Section: Discussionmentioning
confidence: 75%
“…More research is needed in order to explain these differences between isolated spelling and reading disorder. However, recent research has shown that reading and spelling disorder are related to distinct neurocognitive profiles (36). We speculate that these underlying differences in neurocognitive profiles result in behavioral differences and thereby explain the comorbidity between SLD and psychopathological symptoms.…”
Section: Discussionmentioning
confidence: 75%
“…We have argued elsewhere (e.g., Bakos, Landerl, Bartling, Schulte-Körne, & Moll, 2018;Moll & Landerl, 2009), that children with RD store and use orthographic representations during reading, but are slow in processing their phonological form. Thus, reading fluency deficits may result from slow visual-verbal access (Lervåg & Hulme, 2009) and inefficient sequential processing (Jones, Obregón, Kelly, & Branigan, 2008;Protopapas, Katopodi, Altani, & Georgiou, 2018;van Den Boer, Georgiou, & de Jong, 2016).…”
Section: Reading Fluency Deficitsmentioning
confidence: 92%
“…The items were presented in random order, for 5 seconds or until a response occurred, with DMDX (Forster & Forster, 2003). The items were 80 legal and 80 illegal nonwords, taken from Bakos, Landerl, Bartling, Schulte-Körne, and Moll (2018). All items were pronounceable in German.…”
Section: Sensitivity To Frequent Letter Patternsmentioning
confidence: 99%